Agro-industrial waste to biobutanol production: Eco-friendly biofuels for next generation - Huzir, N.M. (Elsevier Ltd, 2018)
Biobutanol offers several merits that make it as top-tier fuels to be discovered. Due to energy and environmental concern, traditional biobutanol production using Acetone-Butanol-Ethanol (ABE) fermentation have been revamped. An important facet for biobutanol production is selection of feedstock as a substrate. Currently, lignocellulosic biomass has attracted much interest globally due to its sustainable supply and non competitiveness with food. Cellulosic biobutanol production can be generated by using lignocellulosic residue such as agricultural crops and residue. Moreover, finding efficient pretreatment is another vital parameter in biobutanol production process. This review will briefly update the recent trends for lignocellulosic biomass as a substrate and feasible pretreatment that can be used for production of biobutanol. Â© 2018 Elsevier Ltd